Characterization of risk factors for early ambulation in paraplegic dogs with absent pain perception undergoing decompressive surgery for thoracolumbar intervertebral disk extrusions - Gomes, Sérgio A.; Alvites, Rui Damásio; Lopes, Bruna; Coelho, André; Targett, Mike; Ribeiro, Jorge; Gouveia, Débora; Martins, Ângela; Varejão, Artur S. P.; Maurício, Ana Colette; Luís, Ana Lúcia (Frontiers in Veterinary Science, 2024)
BackgroundCurrent literature warrants surgical decompression in paraplegic dogs with absent pain perception (APP), but the rate of ambulatory dogs with APP following thoracolumbar (TL) IVDE surgery in a clinical setting remains unknown. Furthermore, the outcome of paraplegic APP French Bulldogs (FBs) is anecdotally considered poor. The aims of this study were threefold within a large population of TL-IVDE paraplegic dogs with APP undergoing decompressive surgery: (1) to characterize early spontaneous pelvic limb movement and ambulation following surgery; (2) to identify risk factors for the recovery of ambulation; and (3) to compare the outcome of FBs and Dachshunds presenting with APP.MethodsA single-center, retrospective case series of dogs with paraplegia and APP diagnosed with TL-IVDE based on CT or MRI, all undergoing surgical decompression (hemilaminectomy ± durotomy). Two main groups were defined: ambulatory and non-ambulatory. These were further characterized depending on the presence of pain perception and spontaneous movement. The outcome was obtained at 4–8 weeks postoperatively. Statistical analysis was performed comparing ambulatory and non-ambulatory dogs and comparing rates of ambulation on FBs vs. Dachshunds.ResultsA total of 127 cases were included, with 77 out of 127 (60.6%) being ambulatory at recheck and 9 out of 127 (7.1%) being ambulatory despite APP. The remaining case distribution of non-ambulatory cases was: with APP (32 out of 127; 25.2%), with pain perception (5 out of 127; 3.9%), and with spontaneous movement (5 out of 127; 3.9%). Multivariate analysis revealed two negative factors for the recovery of ambulation: dogs undergoing hemilaminectomy alongside durotomy (p = 0.003) and dogs presenting with spinal shock (lower motor neuron signs with a lesion higher than the L3–L4 intervertebral disk) characterized by reduced/absent withdrawal reflex (p = 0.008). No difference was found between Dachshunds (n = 41, 73.2% ambulatory) and FBs (n = 33, 63.6% ambulatory) in terms of recovery of ambulation, with only 2 out of 33 (6.1%) FBs developing myelomalacia.ConclusionEarly recovery of ambulation alone (60.6%) and ambulation alongside pain perception (53.5%) occurred in the majority of surgically managed TL-IVDE-affected dogs with APP. Negative prognostic factors for recovery of ambulation were durotomy performed alongside hemilaminectomy, and dogs presenting with spinal shock with reduced/absent withdrawal reflexes, the latter translating to a reduced/absent withdrawal reflexes with a lesion higher than L3–L4 intervertebral disk. Finally, no indications of a worse prognosis for recovery of ambulation or a higher rate of development of myelomalacia in FBs when compared to Dachshunds were found.